KARAKTERISTIK WISATAWAN EROPA SERTA PENGEMBANGAN PARIWISATA BERBASIS KERAKYATAN: STUDI KASUS DESA MUNDUK-BALI - Putu Devi Rosalina; Ni Putu Isha Aprinica; Ni Luh Supartini (Pusat penelitian dan Pengabdian Kepada Masyarakat Politeknik Pariwisata Bali, 2018)
The discrepancy of tourism development which focused only at the south, is now a major focus in tourism development strategies in Bali for equitable distribution of destinations. One touristic village now growing due to is Munduk Tourism Village in North Bali. This study, therefore, aims to obtain the perception of European tourists on the tourism development in Munduk through explorative analysis with 8E model. This research was conducted by using quantitative-qualitative research approach by distributing questionnaires and in-depth interviews to the respondents by accidental sampling. The results show that the tourists are dominated by female with the major countries are from Denmark. The classification of tourists are mostly millenial generation with the age range 17-25 years old, thus they are mostly students. The most enchanting attractions which become favorite preference is Panorama (22%), then followed by authentic Balinese Village (20%). Besides, it also shows that the most effective marketingstrategy is through the internet, as 36% tourists admits to get information from website or social media. Moreover, half of tourists admit for their first visit to Munduk. Another things need to concern is their length of stay which is 2.6 nights. To conclude, there are several challenges and obstacles facing tourism management in Munduk Village, namely: related to culture, local community involvement in cultural attractions, enrichment of cultural attractions to attract tourists and good waste management for sustainable environment.